Organizational Communication Effectiveness in Islamic Educational Institutions - Siregar, Muhammad Fuad Zaini (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
The importance of communication within organizations is expected to contribute to creating a conducive environment. This study is a literature review analyzing theories and studies from academic works such as books, journals, and proceedings. The research findings indicate that effective communication in educational institutions needs to take steps such as: 1) transparency, 2) communication media, and 3) communication skills. The basic principles of effective communication include openness, consistency, etiquette, contextual appropriateness, and empowerment, while some inhibiting factors include information filtering, selective perception, emotions, and language differences. The implication of the article is the necessity for active efforts in creating an environment that supports effective communication in educational institutions.